Steep sulfur gradient in CZTSSe solar cells by H2S-assisted rapid surface sulfurization. Issue 21 (1st April 2021) - Taskesen, Teoman; Pareek, Devendra; Hauschild, Dirk; Haertel, Alan; Weinhardt, Lothar; Yang, Wanli; Pfeiffelmann, Timo; Nowak, David; Heske, Clemens; Gütay, Levent
Abstract : This article demonstrates a flash-type kinetic sulfurization method to introduce band-gap grading in CZTSe based photovoltaic devices. The developed approach allows to achieve a steep grading profile on kesterite thin-film surface. Abstract : Sulfur/selenium grading is a widely used optimization strategy in kesterite thin-film solar cells to obtain a bandgap-graded absorber material and to optimize optical and electrical properties of the solar-cell device. In this work, we present a novel approach to introduce a [S]/([S] + [Se]) grading for Cu2 ZnSn(S, Se)4 solar cells. In contrast to commonly used methods with slow process dynamics, the presented approach aims to create a fast sulfurization reaction on the surface of pure selenide kesterite absorbers by using highly reactive H2 S gas and high sulfurization temperatures in a rapid flash-type process. With a combination of X-ray photoelectron spectroscopy, X-ray emission spectroscopy, Raman spectroscopy, and Raman-shallow angle cross sections spectroscopy, we gain depth-varied information on the [S]/([S] + [Se]) ratio and discuss the impact of different process parameter variations on the material and device properties. The results demonstrate the potential of the developed process to generate a steep gradient of sulfur that is confined mainly to the surface region of the absorber film.